STRUCTURAL AND FUNCTIONAL CHANGES IN THE TWELVE-MONTH-OLD RAT’S SUPRARENAL GLANDS ON SYSTEMATIC EXPOSURE TO HYPERGRAVITY AND UNDER USE OF GLUTARGIN - Moroz, G.A. (World of Medicine and Biology, 2012)
Using light and electron microscopy morphofunctional changes in the suprarenal glands of 24 twelve-month-old Wistar rats were examined. Rats were subjected to systematic exposure of hypergravity (9 g, 10 min) during 10 days. Strongly marked haemodynamic disturbances with stress-induced morphofunctional alterations were revealed. Last one’s appear as features of functional tension of cortical and medullary endocrinocytes and their dystrophy and destruction on submicroscopical level. Application of glutargin was effective. Circulatory disturbances dropped. Regeneration in cortex was potentiated. Ultrastructure of adrenocorticocyte organells responsible for energy production and steroidogenesis was less changed.
Keywords: morphological changes; suprarenal gland; rat; hypergravity; glutargin